Why most authoritarian governments failed while a few succeed: lesson for African countries from miracle economies - Pramanik, Ataul Huq (s.n, 2012)
The study examines the three indicators used to measure success namely, development based on participation manifest through inclusive growth, the appropriate policy reforms in the desired direction supported by the underlying rationality. Depending on the availability of reliable as well as relevant data consistent with our indicators, seventeen African Muslim countries of which five North African and 12 Sub-Sahara countries are selected to empirically test the hypothesis that appropriate and effective policy choices/reforms concomitant with the desired goal of distributive justice matter in the miraculous performance of East-Asian authoritarian cum state-led development model